Arealogical Features of Essential Oil Plants of the Natural Flora of the Foothill Semi-Desert Zone of the Turkestan Region According to the Seasons - IBRAGIMOV, Talgat S.; KUATBAYEV, Askhat T.; SATYBALDIYEVA, Gulmira K.; ALTYBAYEV, Zhaxylyk M.; ORAZBAYEV, Adilkhan Yе. (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019DO - 10.14505//jemt.10.7(39).17, 2020)
The article presents the features of the distribution of essential oil plants of the flora of the foothill semi-desert zone of the Turkestan region, the results of scientific research on the area logical features of the types of essential oil plants in the spring, their stocks are estimated, their scientific and practical value is determined. The leading approach to the study of this problem is the route reconnaissance method, which made it possible to identify 34 contours of the distribution areas of essential oil plants during spring field surveys. The floristic list based on field survey data for the period April-May is 155 species belonging to 106 genera and 34 families. By the number of species in the families prevail: Asterаceae, Fabаceae, Lamiаceae and Brassicаceae. The materials of the article suggest practical significance for university professors of biological specialties and biology students.